A high temperature resistant and high strength aerogel thermal insulation material and a preparation method thereof
By adjusting the ratio of fiber prefabricated parts and sols, and using a multi-process combination method, high-strength and high-toughness aerogel insulation materials were prepared, solving the problem of insufficient performance of existing materials in high-temperature and strong vibration environments, and achieving the improvement of the overall performance of the materials.
Patent Information
- Application Number
- CN202510048977.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-13
AI Technical Summary
The existing aerogel thermal insulation materials cannot meet the comprehensive requirements of high pressure bearing performance, excellent creep resistance, good toughness, low thermal conductivity and low density in high temperature and strong vibration environments.
By changing the components and combination methods of the fiber prefabricated parts, adjusting the sol ratio, vacuum impregnation and supercritical drying processes, combined with atmospheric pressure drying, aerogel composite material with high strength and high toughness was prepared.
It realizes that aerogel thermal insulation materials have high pressure bearing performance, excellent creep resistance and good toughness in high temperature environments, while maintaining low thermal conductivity and low density characteristics, meeting the needs of special applications such as hypersonic aircraft.
Smart Images

Figure CN119430853B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aerogel thermal insulation materials, and specifically relates to a high-temperature resistant and high-strength aerogel thermal insulation material and a preparation method thereof. Background Art
[0002] With the rapid development of hypersonic aircraft technology, the demand for special thermal insulation materials is becoming more and more urgent. The thermal insulation materials at the metal joints of aircraft are in a harsh environment of high temperature and strong vibration. They are not only required to have excellent temperature resistance and heat insulation performance, but also to have high pressure bearing performance, excellent creep resistance and good toughness. Conventional thermal insulation materials cannot meet the above requirements.
[0003] Quartz / quartz ceramic matrix composites have high compressive strength and toughness, but their density reaches 1.5 g / cm 3 Above, the thermal conductivity reaches above 0.25 W / (m·K). Aerogel (such as silica, alumina system) is a new type of high temperature resistant nanoporous material with ultra-low density and excellent thermal insulation performance, but the interaction between its skeleton particles is weak, the mechanical strength is low, and it is fragile, so pure aerogel is usually fiber reinforced. Existing fiber-reinforced aerogel composites have high temperature resistance, low density, low thermal conductivity and certain mechanical strength, but are limited by the intrinsic characteristics of the aerogel matrix and the fiber reinforcement phase. The pressure-bearing performance of aerogel composites is insufficient, the creep resistance and toughness are poor, and they still cannot meet the demanding requirements of special locations.
[0004] How to significantly improve the toughness, pressure bearing performance and creep resistance of aerogel insulation materials while maintaining low density and low thermal conductivity, and to prepare an aerogel insulation material with high temperature resistance, low thermal conductivity and high specific strength, remains a major challenge. Summary of the invention
[0005] In view of the problem that the prior art lacks aerogel composite materials that have both high strength and high toughness and good thermal insulation and temperature resistance, the present invention provides a high-temperature resistant and high-strength and high-toughness aerogel insulation material and a preparation method thereof. By changing the components and combination of fiber preforms and adjusting the sol ratio, the aerogel composite material can achieve high pressure bearing performance, excellent creep resistance (under high-intensity vibration), good toughness (high flexural strength and high bending displacement), low thermal conductivity, low density, and high temperature resistance.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] A method for preparing a high-temperature resistant and high-toughness aerogel thermal insulation material comprises the following steps:
[0008] (1) According to the mass ratio, 50-100 parts of silica sol with a solid content of 10%-50% and 2-5 parts of an acid solution with a concentration of 0.1 mol / L-1 mol / L are mixed and stirred evenly, and allowed to stand for 1h-5h;
[0009] The acid solution is selected from one of sulfuric acid solution, hydrochloric acid solution, nitric acid solution and acetic acid solution;
[0010] (2) Add 0.1 to 3 parts of an alkaline solution having a concentration of 0.5 mol / L to 2 mol / L to the material obtained in the previous step according to the mass ratio, and stir for 10 min to 30 min to obtain a sol;
[0011] The alkaline solution is selected from sodium hydroxide solution, potassium hydroxide solution, barium hydroxide solution, and ammonia water;
[0012] (3) combining the sol obtained in the previous step with the fiber preform by vacuum impregnation, and then aging at 40°C-95°C for 5h-36h;
[0013] The fiber preform is composed of fiber cotton and fiber cloth; wherein the fiber cotton is selected from one of high silica fiber cotton, quartz fiber cotton, alumina fiber cotton, zirconia fiber cotton and mullite fiber cotton; the fiber cloth is selected from one of high silica fiber cloth, quartz fiber cloth, alumina fiber cloth, zirconia fiber cloth and mullite fiber cloth;
[0014] The combination of the fiber preforms includes but is not limited to:
[0015] ①Full fiber cloth (0.05 mm-2 mm, 30 g / m 2 -1800 g / m 2 );
[0016] ②Full fiber cotton (0.05 mm-2 mm, 5 g / m 2 -800 g / m 2 );
[0017] ③ Different surface densities (0.05 mm-2 mm, 5 g / m 2 -800 g / m 2 ) fiber cotton and different surface densities (0.05mm-2 mm, 30 g / m 2 -1800 g / m 2 ) fiber cloths are evenly spaced and stacked;
[0018] ④ Different surface densities (0.05 mm-2 mm, 5 g / m 2 -800 g / m 2) fiber cotton and different surface densities (0.05mm-2 mm, 30 g / m 2 -1800 g / m 2 ) of fiber cloths are stacked at uneven intervals;
[0019] To enhance the bonding strength between layers, all combinations need to be sutured, with a suture spacing of 5mm-100mm;
[0020] (4) The material obtained in the previous step is placed in an oven for drying at a temperature of 120°C-300°C for a time of 12h-96h;
[0021] (5) According to the mass ratio, 50-100 parts of Si-830 sol and 1-8 parts of an acid solution with a concentration of 0.3 mol / L-1.5 mol / L are mixed and stirred evenly, and allowed to stand for 1 h-5 h;
[0022] The acid solution is selected from one of sulfuric acid solution, hydrochloric acid solution, nitric acid solution and acetic acid solution;
[0023] (6) Add 0.2 to 2.5 parts of an alkaline solution with a concentration of 0.5 mol / L to 2 mol / L to the material obtained in the previous step according to the mass ratio, and stir for 10 min to 30 min;
[0024] The alkaline solution is selected from sodium hydroxide solution, potassium hydroxide solution, barium hydroxide solution, and ammonia water;
[0025] (7) combining the material obtained in step (4) with the solution obtained in step (6) by vacuum impregnation, and then aging at 40° C. to 95° C. for 5 h to 36 h;
[0026] (8) The material obtained in the above step is placed in a high-pressure container, and subjected to supercritical drying at 270°C-300°C, 9MPa-13MPa, and pressure maintenance for 2h-24h to obtain a high-temperature resistant and high-strength aerogel insulation material. The high-temperature resistant and high-strength aerogel insulation material has the following typical technical indicators:
[0027] The 3%ε compressive stress is 1.79 MPa-2.23 MPa, the flexural strength is 20.26 MPa-23.88 MPa, the failure displacement is 2.57 mm-2.88 mm, the thermal conductivity at 25℃ is 0.060 W / (m·K)-0.068 W / (m·K), the thermal conductivity at 1100℃ is 0.124 W / (m·K)-0.133 W / (m·K), and the thickness shrinkage at 1100℃ and 1h is 0.6%-0.9%.
[0028] Furthermore, the acid solution in step (5) is preferably an acetic acid solution.
[0029] Furthermore, the alkaline solution in step (6) is preferably a sodium hydroxide solution or a potassium hydroxide solution.
[0030] The present invention also relates to a high-temperature resistant and high-strength aerogel thermal insulation material, which is obtained by the preparation method of the above-mentioned high-temperature resistant and high-strength aerogel thermal insulation material. The high-temperature resistant and high-strength aerogel thermal insulation material has the following typical technical indicators: 3%ε compressive stress is 1.79 MPa-2.23 MPa, flexural strength is 20.26 MPa-23.88 MPa, failure displacement is 2.57 mm-2.88 mm, thermal conductivity at 25°C is 0.060 W / (m·K)-0.068 W / (m·K), thermal conductivity at 1100°C is 0.124W / (m·K)-0.133 W / (m·K), and thickness shrinkage at 1100°C and 1h is 0.6%-0.9%.
[0031] Compared with the prior art, the present invention has the following advantages:
[0032] 1. The method for preparing a high-temperature resistant and high-strength aerogel insulation material described in the present invention only requires two rounds of sol impregnation, and a simple atmospheric pressure drying and a mature supercritical drying process are combined to obtain a high-temperature resistant and high-strength aerogel composite material. Compared with the existing high-strength aerogel composite materials that require multiple impregnations (more than 3 times) and multiple supercritical dryings (more than 3 times), the preparation method is simple and applicable.
[0033] 2. The high-temperature resistant and high-strength aerogel insulation material described in the present invention can enable the aerogel composite material to achieve the comprehensive performance of high pressure bearing performance, excellent creep resistance (under high-intensity vibration), good toughness (high bending strength and high bending displacement), low thermal conductivity, low density and high temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a picture of the high temperature resistant and high strength aerogel insulation material prepared in Example 1 of the present invention before the vibration test;
[0035] Figure 2 This is a diagram of the high temperature resistant and high strength aerogel thermal insulation material prepared in Example 1 of the present invention after vibration testing. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below by way of examples, but these examples should not be considered as limiting the present invention.
[0037] Embodiment 1:
[0038] A method for preparing a high-temperature resistant and high-toughness aerogel thermal insulation material comprises the following steps:
[0039] (1) The thickness is 0.1 mm and the surface density is 20 g / m 2 High silica fiber cotton with a thickness of 0.1mm and a surface density of 56g / m 2 The quartz fiber cloths are evenly stacked and then stitched at a stitching interval of 10 mm to prepare a fiber preform;
[0040] (2) Mix 100 g of silica sol with a solid content of 10% and 2 g of 0.3 mol / L acetic acid solution, stir evenly, and let stand for 1 hour;
[0041] (3) Add 0.5 g of 1 mol / L sodium hydroxide solution and stir for 10 min;
[0042] (4) combining the sol with the fiber preform by vacuum impregnation and then aging at 40 °C for 10 h;
[0043] (5) Place the material in an oven at 200°C and dry for 36 hours;
[0044] (6) Mix 60 g of Si-830 sol and 1 g of 0.3 mol / L acetic acid solution, stir evenly, and let stand for 1 h;
[0045] (7) Add 0.5 g of 0.5 mol / L potassium hydroxide solution to (6) and stir for 10 min;
[0046] (8) combining the material obtained in (5) with the solution obtained in (7) by vacuum impregnation, and then aging at 40°C for 10 h;
[0047] (9) The material obtained in (8) is placed in a high-pressure container and subjected to supercritical drying at 275°C, 9 MPa, and pressure maintenance for 2 h to obtain a high-temperature resistant and high-strength aerogel insulation material.
[0048] The obtained high temperature resistant and high strength aerogel insulation material is in the state before and after the vibration test, where:
[0049] Figure 1 This is a picture of the high temperature resistant and high strength aerogel insulation material prepared in Example 1 before the vibration test;
[0050] Figure 2 This is a picture of the high temperature resistant and high strength aerogel insulation material prepared in Example 1 after vibration testing.
[0051] Embodiment 2:
[0052] A method for preparing a high-temperature resistant and high-toughness aerogel thermal insulation material comprises the following steps:
[0053] (1) The thickness is 0.2 mm and the surface density is 45 g / m 2Quartz fiber wool with a thickness of 0.2mm and a surface density of 109g / m 2 Alumina fiber cloths are evenly stacked and then stitched at a stitching interval of 30 mm to prepare a fiber preform;
[0054] (2) Mix 80 g of silica sol with a solid content of 20% and 3 g of 0.3 mol / L acetic acid solution, stir evenly, and let stand for 3 hours;
[0055] (3) Add 0.8 g of 1 mol / L sodium hydroxide solution and stir for 20 min;
[0056] (4) combining the sol with the fiber preform by vacuum impregnation and then aging at 40 °C for 15 h;
[0057] (5) Place the material in an oven at 200°C and dry for 36 hours;
[0058] (6) Mix 75 g of Si-830 sol and 2 g of 0.5 mol / L acetic acid solution, stir evenly, and let stand for 3 h;
[0059] (7) Add 0.8 g of 0.6 mol / L sodium hydroxide solution to (6) and stir for 20 min;
[0060] (8) combining the material obtained in (5) with the solution obtained in (7) by vacuum impregnation, and then aging at 45°C for 24 h;
[0061] (9) The material obtained in (8) is placed in a high-pressure container and subjected to supercritical drying at 285°C, 10 MPa, and pressure maintenance for 4 h to obtain a high-temperature resistant and high-strength aerogel insulation material.
[0062] Embodiment 3:
[0063] A method for preparing a high-temperature resistant and high-toughness aerogel thermal insulation material comprises the following steps:
[0064] (1) The thickness is 0.6 mm and the surface density is 120 g / m 2 Mullite fiber wool with a thickness of 0.8mm and a surface density of 652g / m 2 The oxidized pick fiber cloths are stacked at uneven intervals and then stitched at a stitching interval of 60 mm to prepare a fiber preform;
[0065] (2) Mix 60 kg of silica sol with a solid content of 30% and 5 g of 0.5 mol / L hydrochloric acid solution, stir evenly, and let stand for 1 hour;
[0066] (3) Add 1 g of 0.8 mol / L sodium hydroxide solution and stir for 30 min;
[0067] (4) combining the sol with the fiber preform by vacuum impregnation and then aging at 60 °C for 36 h;
[0068] (5) Place the material in a 300°C oven and dry for 72 hours;
[0069] (6) Mix 100 kg of Si-830 sol and 4 g of 0.5 mol / L acetic acid solution, stir evenly, and let stand for 5 hours;
[0070] (7) Add 0.3 g of 1.2 mol / L sodium hydroxide solution to (6) and stir for 30 min;
[0071] (8) combining the material obtained in (5) with the solution obtained in (7) by vacuum impregnation, and then aging at 60° C. for 36 h;
[0072] (9) The material obtained in (8) is placed in a high-pressure container and subjected to supercritical drying at 295°C, 12 MPa, and pressure maintenance for 10 h to obtain a high-temperature resistant and high-strength aerogel insulation material.
[0073] Embodiment 4:
[0074] A method for preparing a high-temperature resistant and high-toughness aerogel thermal insulation material comprises the following steps:
[0075] (1) The thickness is 0.8 mm and the surface density is 170 g / m 2 Zirconia fiber cotton with a thickness of 0.4mm and a surface density of 402g / m 2 The quartz fiber cloths are stacked at uneven intervals and then stitched at a stitching interval of 100 mm to prepare a fiber preform;
[0076] (2) Mix 50 g of silica sol with a solid content of 40% and 1 g of 0.5 mol / L nitric acid solution, stir evenly, and let stand for 1 hour;
[0077] (3) Add 1 g of 1 mol / L sodium hydroxide solution and stir for 10 min;
[0078] (4) combining the sol with the fiber preform by vacuum impregnation and then aging at 40 °C for 24 h;
[0079] (5) Place the material in a 300°C oven and dry for 72 hours;
[0080] (6) Mix 100 g of Si-830 sol and 4 g of 0.5 mol / L acetic acid solution, stir evenly, and let stand for 5 h;
[0081] (7) Add 0.3 g of 1.2 mol / L sodium hydroxide solution to (6) and stir for 10 min;
[0082] (8) combining the material obtained in (5) with the solution obtained in (7) by vacuum impregnation, and then aging at 40°C for 36 h;
[0083] (9) The material obtained in (8) is placed in a high-pressure container and subjected to supercritical drying at 295°C, 12 MPa, and pressure maintenance for 15 h to obtain a high-temperature resistant and high-strength aerogel insulation material.
[0084] Comparative Example 1:
[0085] The preparation method of aerogel thermal insulation material comprises the following steps:
[0086] (1) The thickness is 1 mm and the surface density is 250 g / m 2 Mullite fiber wool is stacked and then stitched at a stitching interval of 10 mm to prepare a fiber preform;
[0087] (2) Mix 100 g of silica sol with a solid content of 10% and 2 g of 0.3 mol / L acetic acid solution, stir evenly, and let stand for 1 hour;
[0088] (3) Add 0.5 g of 1 mol / L sodium hydroxide solution and stir for 10 min;
[0089] (4) combining the sol with the fiber preform by vacuum impregnation and then aging at 40 °C for 10 h;
[0090] (5) Place the material in an oven at 200°C and dry for 36 hours;
[0091] (6) Mix 60 g of Si-830 sol and 1 g of 0.3 mol / L acetic acid solution, stir evenly, and let stand for 1 h;
[0092] (7) Add 0.5 g of 0.5 mol / L potassium hydroxide solution to (6) and stir for 10 min;
[0093] (8) combining the material obtained in (5) with the solution obtained in (7) by vacuum impregnation, and then aging at 40°C for 10 h;
[0094] (9) The material obtained in (8) is placed in a high-pressure container and subjected to supercritical drying at 275°C, 9 MPa, and pressure maintenance for 2 h to obtain the target composite material.
[0095] Comparative Example 2:
[0096] The preparation method of aerogel thermal insulation material comprises the following steps:
[0097] (1) The thickness is 1 mm and the surface density is 840 g / m 2 Mullite fiber wool is stacked and then stitched at a stitching interval of 10 mm to prepare a fiber preform;
[0098] (2) Mix 60 g of silica sol with a solid content of 30% and 5 g of 0.5 mol / L hydrochloric acid solution, stir evenly, and let stand for 1 hour;
[0099] (3) Add 1 g of 0.8 mol / L sodium hydroxide solution and stir for 30 min;
[0100] (4) combining the sol with the fiber preform by vacuum impregnation and then aging at 60 °C for 36 h;
[0101] (5) Place the material in a 300°C oven and dry for 72 hours;
[0102] (6) Mix 100 g of Si-830 sol and 4 g of 0.5 mol / L acetic acid solution, stir evenly, and let stand for 5 h;
[0103] (7) Add 0.3 g of 1.2 mol / L sodium hydroxide solution to (6) and stir for 30 min;
[0104] (8) combining the material obtained in (5) with the solution obtained in (7) by vacuum impregnation, and then aging at 60° C. for 36 h;
[0105] (9) The material obtained in (8) is placed in a high-pressure container and subjected to supercritical drying at 295°C, 12 MPa, and pressure maintenance for 10 h to obtain the target composite material.
[0106] result:
[0107] The performance test results are shown in Table 1:
[0108] Table 1 Performance test results
[0109]
[0110] Vibration test:
[0111] The application environment was simulated and the environmental simulation test was carried out. The vibration test conditions are shown in Table 2 and the vibration test results are shown in Table 3. The test sample was fixedly connected to the vibration table with an adapter plate (stainless steel plate), and the sample and the adapter plate were fixedly connected with screws and nuts, with a torque of 5 N·m.
[0112] Table 2 Vibration test conditions
[0113]
[0114] Table 3 Vibration test results
[0115]
[0116] analyze:
[0117] 1. Compared with comparative example 1, the failure displacement of embodiments 1-4 is nearly 5 times that of comparative example 1, indicating that the toughness of the composite material can be significantly enhanced by the combination of fiber cloth and fiber cotton and their different combination methods, and there will be no significant effect on its compression, bending strength, thermal conductivity, etc.
[0118] 2. The 1100°C and 1h thickness shrinkage data of Examples 1-4 and Comparative Examples 1-2 are both less than 1%, which indicates that the composite material prepared by this method has excellent temperature resistance.
[0119] 3. The performance comparison between Examples 1-4 and Comparative Example 2 shows that if the composite fiber is in the form of a full fiber cloth, although the toughness (failure displacement) and bending strength will be significantly enhanced, the density and thermal conductivity will also be greatly increased.
[0120] 4. Through the comparison of vibration tests, it can be seen that by comparing Examples 1-4 with Comparative Example 1, the combination of fiber cloth and fiber cotton and their different combinations can reduce the mass loss rate and thickness shrinkage rate of the material after vibration; by comparing Examples 1-4 with Comparative Examples 1 and 2, it can be seen that with the increase of the fiber cloth content in the composite material, the mass loss rate and thickness shrinkage rate of the material after vibration will decrease.
[0121] The above are only preferred implementations of the present invention. The protection scope of the present invention is not limited to the above embodiments. Various process schemes that are not substantially different from the concept of the present invention are within the protection scope of the present invention.
Claims
1. A method for preparing a high temperature resistant and high strength aerogel thermal insulation material, characterized in that: The following steps are involved: (1) According to the mass ratio, 50-100 parts of silica sol with a solid content of 10%-50% and 2-5 parts of an acid solution with a concentration of 0.1 mol / L-1 mol / L are mixed and stirred evenly, and allowed to stand for 1h-5h; The acid solution is selected from one of sulfuric acid solution, hydrochloric acid solution, nitric acid solution and acetic acid solution; (2) Add 0.1 to 3 parts of an alkaline solution having a concentration of 0.5 mol / L to 2 mol / L to the material obtained in the previous step according to the mass ratio, and stir for 10 min to 30 min to obtain a sol; The alkaline solution is selected from sodium hydroxide solution, potassium hydroxide solution, barium hydroxide solution, and ammonia water; (3) combining the sol obtained in the previous step with the fiber preform by vacuum impregnation, and then aging at 40°C-95°C for 5h-36h; The fiber preform is composed of fiber cotton and fiber cloth; wherein the fiber cotton is selected from one of high silica fiber cotton, quartz fiber cotton, alumina fiber cotton, zirconia fiber cotton and mullite fiber cotton; the fiber cloth is selected from one of high silica fiber cloth, quartz fiber cloth, alumina fiber cloth, zirconia fiber cloth and mullite fiber cloth; The fiber preforms are assembled in the following manner: ①Specifications: 0.05 mm-2 mm, 5 g / m 2 -800 g / m 2 The fiber cotton with specifications of 0.05 mm-2 mm, 30 g / m 2 -1800 g / m 2 The fiber cloths are evenly spaced and stacked; ②Specifications: 0.05 mm-2 mm, 5 g / m 2 -800 g / m 2 The fiber cotton with specifications of 0.05 mm-2 mm, 30 g / m 2 -1800 g / m 2 The fiber cloth is superimposed at uneven intervals; All combinations need to be sutured to enhance the bonding strength between layers, and the suture spacing is 5mm-100mm; (4) The material obtained in the previous step is placed in an oven for drying at a temperature of 120°C-300°C for a time of 12h-96h; (5) According to the mass ratio, 50-100 parts of Si-830 sol and 1-8 parts of an acid solution with a concentration of 0.3 mol / L-1.5 mol / L are mixed and stirred evenly, and allowed to stand for 1 h-5 h; The acid solution is selected from one of sulfuric acid solution, hydrochloric acid solution, nitric acid solution and acetic acid solution; (6) Add 0.2 to 2.5 parts of an alkaline solution having a concentration of 0.5 mol / L to 2 mol / L to the material obtained in the previous step according to the mass ratio, and stir for 10 min to 30 min; The alkaline solution is selected from sodium hydroxide solution, potassium hydroxide solution, barium hydroxide solution, and ammonia water; (7) combining the material obtained in step (4) with the solution obtained in step (6) by vacuum impregnation, and then aging at 40° C. to 95° C. for 5 h to 36 h; (8) The material obtained in the above step is placed in a high-pressure container, and subjected to supercritical drying at 270°C-300°C, 9MPa-13MPa, and pressure maintenance for 2h-24h to obtain a high-temperature resistant and high-strength aerogel insulation material. The high-temperature resistant and high-strength aerogel insulation material has the following typical technical indicators: The 3%ε compressive stress is 1.79 MPa-2.23 MPa, the flexural strength is 20.26 MPa-23.88 MPa, the failure displacement is 2.57 mm-2.88 mm, the thermal conductivity at 25℃ is 0.060 W / (m·K)-0.068 W / (m·K), the thermal conductivity at 1100℃ is 0.124W / (m·K)-0.133 W / (m·K), and the thickness shrinkage at 1100℃ and 1h is 0.6%-0.9%.
2. The method for preparing a high temperature resistant and high toughness aerogel thermal insulation material according to claim 1, characterized in that: The acid solution described in step (5) is selected from acetic acid solution.
3. The method for preparing a high temperature resistant and high toughness aerogel thermal insulation material according to claim 1, characterized in that: The alkaline solution described in step (6) is selected from sodium hydroxide solution or potassium hydroxide solution.
4. A high temperature resistant and high strength aerogel thermal insulation material, characterized in that: The high temperature resistant and high strength aerogel insulation material is prepared by the method for preparing the high temperature resistant and high strength aerogel insulation material according to any one of claims 1 to 3, and the high temperature resistant and high strength aerogel insulation material has the following typical technical indicators: 3%ε compressive stress is 1.79 MPa-2.23 MPa, flexural strength is 20.26 MPa-23.88 MPa, failure displacement is 2.57 mm-2.88 mm, thermal conductivity at 25°C is 0.060 W / (m·K)-0.068 W / (m·K), thermal conductivity at 1100°C is 0.124 W / (m·K)-0.133 W / (m·K), and thickness shrinkage at 1100°C and 1h is 0.6%-0.9%.
Citation Information
Patent Citations
Rock wool fiber-reinforced silicon oxide-based high-strength thermal-insulation composite material and preparation method thereof
CN111454071A
Method for improving high-temperature heat insulation performance of nano-porous heat insulation material
CN112047711A